Partisipasi Masyarakat dalam Pengembangan Wisata Pertanian Organik di Desa Gentungan, Kecamatan Mojogedang, Kabupaten Karanganyar - Vanesa Della Ferdiana; Emi Widiyanti; Putri Permatasari (Universitas Sebelas Maret, 2024)
Gentungan Village organic tourism is an educational and practical tourism in organic farming and Embung Setumpeng tourism. Gentungan Village organic tourism applies the concept of community-based tourism (CBT) which emphasizes the participation of local communities. Community participation is an activity of a person or group of people to be directly or indirectly involved in providing ideas or ideas on a development program. This study aims to analyze the stages and forms of community participation in the development of organic farming tourism in Gentungan Village, Mojogedang Sub-district, Karanganyar Regency. This research uses a qualitative analysis method with a descriptive approach, using data sources obtained through in-depth interviews, observation, and documentation. The data analysis method uses Miles and Huberman’s interactive analysis. The results showed that there are 3 stages of community participation, namely (1) the planning stage, where the community is involved in community meeting activities, community involvement in the planning stage shows their participation in the form of time and thoughts contributed voluntarily. (2) The implementation stage, where the community is involved in the implementation of tourism activities. The Gentungan Village community is actively involved in addition to the community service activities of the tourist attractions, some residents become parking attendants and many people sell at the Embung Setumpeng location. Some people are also involved in comparative study activities by becoming presenters, outbound guides, and operators. (3) The stage of enjoying the results, where the community feels economic benefits with an increase in income and social benefits with an increase in mutual cooperation and the quality of human resources from tourism activities.